Case–control Study of the Stressful Life Events in Patients with Alcohol Use Disorder - Kanaujiya N. Kumar; Patel Roshani; Jhala Vaishnavi; Patel Harita; J Samani Mukesh (Taiwanese Journal of Psychiatry)
Objective: Exposure to stress is potentially important in the pathway to alcohol consumptions and alcohol use disorders (AUDs). Stressors occur at multiple time points across the life course, with varying degrees of chronicity and intensity. In this study, we intended to compare the stressful life events, in patients with AUD and control group. Methods: A comparative, cross-sectional study was done on 100 male patients with AUD in outpatient clinics of psychiatric department and 100 male patients with minor illness in outpatient clinics of other departments. All the patients were clinically evaluated through history and mental status examination, and diagnosis of AUD was confirmed using DSM-V diagnostic criteria. The alcohol use identification test was used to all AUD patients to assess the severity of AUD. Presumptive Stressful Life Effects Scale was used in both groups to assess stressful life events. Results: We found that patients with AUD had significant increased alcohol use in response to exposure to stressful life events than those of the corresponding to controls (p < 0.001). Stressful life events such as family and marital conflicts and job loss significantly increased the risk of AUD (p < 0.001). Conclusion: Results suggest the central importance of stressful life events is a risk among AUD. These findings have implications for both the assessment and the treatment of individuals who present with AUDs.